PERSEPSI DAN RESPON MAHASISWA UNIVERSITAS PRIMA INDONESIA MENGENAI PERNIKAHAN WANITA HAMIL LUAR NIKAH DI ERA MILLENIALS - said Rizal (DIKTUM: Jurnal Syariah dan Hukum, 2020)
Abstract: Marriage is mandated so that humans have descendants and legitimate families leading to a happy life in the afterlife under the auspices of love and divine pleasure. But as for those who violated the shari'a ties of this sacred marriage, by tarnishing it in the form of adultery or intimate relationships outside of marriage. Adultery in the millennial era today is no longer taboo, fast-growing fast-food information is easily accessed in the form of information media, television, internet, YouTube, and the vulgar content that is displayed can have implications for our young generation who were originally then try to fall into things that are not cold in the form of early marriage, marriage outside pregnancy marriage. The purpose of this study was to determine the perceptions and responses of Prima Indonesia University students about the Marriage of Unmarried Pregnant Women in the Millennial Era. The results of the study show that students' perceptions about the statement of marriage of pregnant women out of wedlock as all students have known that the marriage of pregnant women out of wedlock is the marriage of pregnant women before the marriage contract. The students' responses to the marriage of pregnant women before the marriage contract are a result of the results of adultery which began from promiscuity, the presence of vulgar content, strengthening pemahan will be a weak religion, less control from parental supervision. As for the marriage of pregnant women out of wedlock it is also due to the current lifestyle trends in the lifestyle labeled Brand need a high boarding house to fulfill them. With the current socialite style can affect the life needs of someone who is not a problem if he is financially able but what about the financially incapable.